PENINGKATAN KEMAMPUAN MENGAPRESIASI PUISI MELALUI LATAR PEMBACAAN PUISI DALAM VIDEO COMPACT DISK (VCD) PADA SISWA SMA NEGERI 15 SEMARANG - Qomariyah, U'um (Universitas Negeri Semarang, 2010)
Poetry is one of literary works which is interesting and complicated as well.Based on the observation, most Senior High School Students found it difficult toappreciate poetry. In this case,Video Compact Disk (VCD) of poetry reading is able tobe functioned as an alternative way to increase students' appreciation capability. Thisresearch studied the effectiveness ofVideo Compact Disk of setting of poetry readingin an attempt to increase student's appreciation. This research is a quasy experimentwhich combined qualitative and quantitative methods. The data were obtainedthrough pre test and post test to the experimental and control groups. Based on chartand T test, it can be proved that the result of student's poetry appreciation learning byVideo Compact Disk increased.Kata kunci : latar, pembacaan puisi,VCD, apresiasi puisi